Two zinc metal–organic framework isomers based on pyrazine tetracarboxylic acid and dipyridinylbenzene for adsorption and separation of CO2 and light hydrocarbons. Issue 4 (2nd January 2020) - Ye, Yu; Du, Jianfeng; Sun, Libo; Liu, Yuchuan; Wang, Shun; Song, Xiaowei; Liang, Zhiqiang
Abstract : Two zinc metal–organic framework isomers were designed and constructed using 2, 3, 5, 6-tetrakis(4-carboxyphenyl)pyrazine and dipyridinylbenzene as co-ligands for gas adsorption and separation. Abstract : Two highly porous metal–organic framework isomers Zn2 (TCPP)(DPB) (1 and 2, H4 TCPP = 2, 3, 5, 6-tetrakis(4-carboxyphenyl)pyrazine and DPB = 1, 4-di(pyridin-4-yl)benzene) were successfully synthesized using different solvents and acid species to adjust the topologies of these two MOFs. Both of them were constructed by paddlewheel Zn2 (COO)4, TCPP 4−, and DPB ligands. In compound 1, the Zn2 (COO)4 paddlewheel units were fitted together by the TCPP 4− ligands to form two-dimensional layers, which were further connected by DPB ligands as pillars to construct a two-fold catenated 3D framework. In compound 2, the cross-linkage of Zn2 (COO)4 paddlewheel units and TCPP 4− ligands resulted in a three-dimensional framework of Zn-TCPP, in which DPB ligands coordinated to two axial vertical dinuclear Zn2 (COO)4 . Both activated MOFs exhibited permanent porosity with high BET areas (1324 m 2 g −1 for 1 and 1247 m 2 g −1 for 2 ) and possessed narrow pore size distributions (0.93 nm for 1 and 1.02 nm for 2 ). Moreover, the adsorption behaviors of the two activated MOFs for CO2 and light hydrocarbons (C1, C2, and C3) at low pressure were evaluated and favorable selectivity was proven for C3 H8 /C3 H6 over CH4 . These two MOF materials reported in this study for selective CO2 and light hydrocarbon capture have immense potential applications for environmental protection.